The Effect Of Sustainability Report Disclosure On Profitability In Banking Companies Listed On The Indonesia Stock Exchange - Simamora, Masrowaty Rebecca; Andayani, Wuryan (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
The fluctuating profitability of banking companies in recent years is reflected on the ROA percentage during the 2017-2022 period. This study aims to determine the effect of sustainability report disclosure on profitability, involving 78 samples from 26 banking companies listed on the Indonesia Stock Exchange between 2021 and 2023, selected through purposive sampling based on established criteria. The secondary data collected from annual reports and sustainability reports are analyzed quantitatively by multiple regression processed by Statistical Package for Social Science (SPSS) software. The test results exhibit that the sustainability report disclosure for economic and environmental aspects has no effect on profitability, while that for social aspect has a positive effect on profitability. The results of this study strengthen the legitimacy theory which provides empirical evidence that the disclosure of social aspects in the sustainability report can increase profitability.